HUBUNGAN STATUS GIZI DENGAN PEKEMBANGAN MOTORIK KASAR ANAK USIA TODDLER (1-3 TAHUN) DI WILAYAH KERJA PUSKESMAS PAUH PADANG TAHUN 2017 - Yelly Herien (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Toddler is an age group that shows rapid growth so it needs more attention to itsdevelopmental condition. One aspect of development is gross motor development. Based on data,there are still many toddlers who experience delays in their development especially in gross motordevelopment. There are many factors that can affect the delays in gross motor development andone of them is the nutritional status. This study aims to determine the relationship betweennutritional status with gross motor development of toddler (1-3 years) in the Work Area PublicHealth Center Pauh Padang Year 2017. The type of this research was analytical survey with crosssectional study approach. Data was collected on 15 Mei to 9 June 2017. The sample of thisresearch was 59 children. Sampling technique was purposive sampling. Data was collected byobservation and questionnaire. Data analysis technique is univariate and bivariate analysis. Datawas processed by computerized with Chi-Square test. Based on the results of this study, 35,6% ofchildren have nutritional status of lean, and there is 22,3% doubted in gross motor developmenttest. There is no correlation between nutritional status with gross motor development (p value =0,739). This research can be a basic information for health care providers that besides nutritionalstatus and stimulation there are many factors which may affect gross motor develompment ofchildren. Therefore,it is expected for health care providers to remain monitor child’s gross motordevelompment by looking at the related factors.Key Words : Nutritional Status, Stimulation, Gross Motor Development